Melintasi Batas Tradisional: Integrasi Teknologi dalam Pendidikan Agama Kristen - Fredik Melkias Boiliu; Yasrid Prayogo Kurniawan; Sari Handayani (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
Christian religious education has experienced a significant shift along with technological advances in contemporary society. This research will discuss the integration of technology in the context of Christian religious education by highlighting the challenges and opportunities that arise from this paradigm shift. This research uses descriptive qualitative methods with literature review. The results of this research will explore how technology is used to expand traditional boundaries in Christian religious learning through wider access, greater interactivity, and deeper learning experiences for students. In addition, it outlines the integration of appropriate technology, contextual, situational, relevant and dynamic Christian religious education in meeting the spirituality and morality needs of students in this digital era.